2013
DOI: 10.1039/c3sm50532d
|View full text |Cite
|
Sign up to set email alerts
|

Roles of chemical pattern period and film thickness in directed self-assembly of diblock copolymers

Abstract: We develop a new numerical self-consistent field theory (SCFT) scheme for examining thin film nanostructures of cylinder-forming AB diblock copolymers on a chemically patterned substrate. Using this, we make a systematic analysis to achieve a fundamental understanding of the model system, and the conditions to create various novel film morphologies are scrutinized by varying the pattern period and film thickness. At a fixed pattern period, eight candidate phases which are divided into two groups according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…2 View Article Online target morphologies of the 1HnV phase (n = 1, 2, 3 and 4) at the parameter set which minimizes the free energy for the given morphology. 42 In the most preferable period, we get L 1H1V It is interesting that for each 1HnV phase, many similar morphologies are found which we may collectively call a 1HnV family, and the difference between each member of the family is mainly the relative position of vertical cylinders across the horizontal hemicylinder. This is in agreement with the experimental results, 40,44,47 and the case for 1H1V was intensely analyzed in the previous simulation.…”
Section: Optimal Conditions For 1hnvmentioning
confidence: 95%
See 4 more Smart Citations
“…2 View Article Online target morphologies of the 1HnV phase (n = 1, 2, 3 and 4) at the parameter set which minimizes the free energy for the given morphology. 42 In the most preferable period, we get L 1H1V It is interesting that for each 1HnV phase, many similar morphologies are found which we may collectively call a 1HnV family, and the difference between each member of the family is mainly the relative position of vertical cylinders across the horizontal hemicylinder. This is in agreement with the experimental results, 40,44,47 and the case for 1H1V was intensely analyzed in the previous simulation.…”
Section: Optimal Conditions For 1hnvmentioning
confidence: 95%
“…For the actual evaluation of the modified diffusion equation, we use a real space SCFT method improved by Yang et al, 42 which is known to eliminate the material conservation problem found in most real space methods. Although Z i (x,y) can accommodate any two dimensional pattern, the stripe geometry treated in this work makes it only a function of x.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 3 more Smart Citations